Entering tennis men`s Grand Slams within the top-10 and its relationship with the fact of winning the tournament - Prieto-Bermejo, J.; Gomez-Ruano, M. A. (Revista Internacional de Ciencias del Deporte, 2016)
The purpose of this study was to analyse the relationship between entering tennis men`s singles Grand Slams within the top-10 ranking (i.e. title favourites) and the fact of winning the tournament. In order to differentiate between these players in a more powerful way than just considering the ranking number, a cluster algorithm was used to classify the players into two groups depending on their number of ranking points (i.e. higher level top-10 players vs. lower level top-10 players). The possible winners entering the tournament outside the top-10 (if any) were also considered. The sample comprised all the 92 men`s singles Grand Slams played between 1990 and 2012. As was expected, the majority of Grand Slams were won by players entering the tournament ranked in the top-10. However, the main result is contrary to the hypothesis that there would be significant differences in the number of titles won in favour of the players entering the tournament from the higher positions of the top-10 when comparing to those won by the players entering from the lower positions of the top-10. Several factors that may influence whether and to what extent a player is more or less favourite to win a Grand Slam title are presented in the discussion.